KAJIAN TIPOLOGIS KENDI TANAH LIAT SITUS GEDUNGKARYA, JAMBI, DAN PERSAMAANNYA DI ASIA TENGGARA - Budianto Hakim (Balai Arkeologi Provinsi Sulawesi Selatan, 2001)
The background of pot as one of pottery development could be understood in two aspects: commerce, inter-cultural relations, and language. An enormous pot made from clay at Gedungkarya site is a new issue. Where this pot does came from? And, whether Gedungkarya site is an 'industry' or not? Hitherto the question still under debates for white clay pots distribution includes wide areas in South East Asia. A typology study to compare with South East Asia pots is an effort to answer the question above.